2023
DOI: 10.1177/2212585x231169740
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the impact of the “double reduction” policy on the educational processes of Chinese students studying in Europe

Abstract: The relevance of the stated topic of scientific research is determined by the presence of many problems associated with the need to study the impact of the “double reduction” policy on the educational processes of Chinese students who are educated in Europe. This research work is aimed at studying the features of the “double reduction” policy, its advantages and disadvantages, as well as its impact on the educational processes of Chinese students studying in European educational institutions. The basis of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…These deeply ingrained stereotypes and cultural norms position girls in rural multi-child families as sacrificial figures in terms of educational opportunities, thereby obstructing their access to higher degrees and educational success. As a result, the gap in educational attainment between genders in rural China continues to widen, perpetuating a cycle of inequality [19].…”
Section: Gender Traditionmentioning
confidence: 99%
“…These deeply ingrained stereotypes and cultural norms position girls in rural multi-child families as sacrificial figures in terms of educational opportunities, thereby obstructing their access to higher degrees and educational success. As a result, the gap in educational attainment between genders in rural China continues to widen, perpetuating a cycle of inequality [19].…”
Section: Gender Traditionmentioning
confidence: 99%
“…As indicated in the study of Medina-Jerez (2018), the prevalence of HPE & NOS in Latin America's science education research was closely tied with national investment. Furthermore, with the release of "double reduction" policy in 2022 (She et al, 2023), mainly targeting to reduce students' burden of homework and after-school courses in compulsory education, the inequalities in Chinese education system and students' welfare have attracted much attention. It appears that a call for further attentions into teachers' development, individual, social and cultural difference, and approaches to assist individual's development (e.g., technology-assisted science education), is justified.…”
Section: N Referencesmentioning
confidence: 99%
“…Although the original intention of the Chinese government to regulate the extracurricular tutoring industry is to achieve the goal of common prosperity and equal distribution of educational resources by prohibiting the capitalization of education [3]. Some researchers also pointed out that this national policy has led to the crisis of millions of experienced teachers facing unemployment and millions of graduates unable to find jobs [2,4]. The author found that many researchers have studied and analyzed this policy from the perspective of education policy.…”
Section: Introductionmentioning
confidence: 99%